2012
DOI: 10.4012/dmj.2012-061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a coating resin containing S-PRG filler to prevent demineralization of root surfaces

Abstract: The purpose of this study was to evaluate the ability of a coating material containing the surface pre-reacted glass-ionomer (S-PRG) filler to protect the root from demineralization in vitro. The proprietary coating resin containing the S-PRG filler (PRG Barrier Coat) was applied to human root dentin and immersed in acid buffer at pH 4.5 for 3 d. Demineralization was evaluated by micro-CT scanning and the dentin-material interface observed by scanning electron microscopy. The ability of the coating resin to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 47 publications
3
62
0
5
Order By: Relevance
“…Ions released from the S-PRG filler were suggested to promote apatite induction [17], increase dentine remineralization [44] and improve dentine acid resistance [45]. Furthermore, S-PRG based root canal sealer was able to establish a superficial surface layer in root canal dentine that is rich with fluoride, strontium, and silicon [45]. This study also confirms the findings of previous studies that showed continuous release of calcium ions from MTA [2,46].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Ions released from the S-PRG filler were suggested to promote apatite induction [17], increase dentine remineralization [44] and improve dentine acid resistance [45]. Furthermore, S-PRG based root canal sealer was able to establish a superficial surface layer in root canal dentine that is rich with fluoride, strontium, and silicon [45]. This study also confirms the findings of previous studies that showed continuous release of calcium ions from MTA [2,46].…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies also showed that the combination of fluoride and strontium caused a synergistic remineralization effect [42,43]. Ions released from the S-PRG filler were suggested to promote apatite induction [17], increase dentine remineralization [44] and improve dentine acid resistance [45]. Furthermore, S-PRG based root canal sealer was able to establish a superficial surface layer in root canal dentine that is rich with fluoride, strontium, and silicon [45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it seals the lesion and prevents caries. 42 A combination of casein phosphopeptide and amorphous calcium phosphate (CCP-ACP) and photo activated disinfection (PAD) proved to be very effective and holds great potential as a recommended treatment for stabilizing root surface caries in the clinical practice. 43 Healozone has been proposed as a method of reversing, arresting or slowing down the progression of dental caries.…”
Section: Prevention Of Root Cariesmentioning
confidence: 99%
“…Several properties can be proposed as useful "bio-active" functions for restorative materials. One major approach involves addition of "bio-protective" effects such as control of bacterial infection 1,2) , strengthening of the tooth substrate 3,4) , prevention of demineralization 2,5) , or protection of interfacial deterioration [6][7][8] . The other approach involves conferring "bio-promoting" effects such as remineralizing effects 9,10) , control of inflammation, or promotion of tissue regeneration 11) .…”
Section: Introductionmentioning
confidence: 99%